SOLUTION
To do this, we make y the subject of formula in the equation
![-5x+3y=-12](https://img.qammunity.org/2023/formulas/mathematics/college/rczpe820j6kujr5802y2aadieuay3fxgmm.png)
This becomes
![\begin{gathered} -5x+3y=-12 \\ 3y=-12+5x \\ 3y=5x-12 \\ y=(5)/(3)x-(12)/(3) \\ y=(5)/(3)x-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4ub6vohldv0ixsqpbmtry5kt7e3tegedrw.png)
Above the line is usually greater than or equal to, while below the line is less than or equal to.
Hence the inequality is
![y\leq(5)/(3)x-4](https://img.qammunity.org/2023/formulas/mathematics/college/ayd56q6gn374sht4rse9uam5wjvskob0yk.png)
Less than or equal to, because it is a solid line and not a broken line
So, the answer becomes
![y\leq(5)/(3)x-4](https://img.qammunity.org/2023/formulas/mathematics/college/ayd56q6gn374sht4rse9uam5wjvskob0yk.png)